Scientific products in psychology and deafness in the state of Pernambuco (Research, Society and Development, 2020)
This article aimed to describe the scientific production in psychology about deafness in the state of Pernambuco (PE). With a brief historical overview and the studies of deafness psychology in order to understand how the deaf subject was included in society and in the area of psychological research, the article brings a literature review from databases (CAPES, LILACS, Scielo) using the terms psychology, deaf, deafness and Pernambuco. It is understood that the discussion on this topic is under development in the national territory, although the trajectory of psychology and studies of the deaf community are recent.